State of Oral Mucosa as an Additional Symptom in the Course of Primary Amyloidosis and Multiple Myeloma Disease - Maciej R. Czerniuk; Artur Jurczyszyn; Grzegorz Charlinski (Case Reports in Medicine)
Multiple myeloma (myeloma multiplex (MM)) is a malignant non-Hodgkin’s lymphoma derived from B cell. Its essence is a malignant clone of plasma cells synthesizing growth of monoclonal immunoglobulin, which infiltrate the bone marrow, destroy the bone structure, and prevent the proper production of blood cells components. The paper presents a case of 62-year-old patient who developed symptoms in addition to neurological and haematological changes in the oral mucosa in the course of multiple myeloma. The treatment resulted in partial improvement. The authors wish to draw attention not only to nonspecificity and rarity of changes in the mouth which can meet the dentist but also to the complexity of the multidisciplinary therapy patients diagnosed with MM.